Developing A Controlled Vocabulary for Curriculum Mapping: A Case Study. Issue 2 (3rd April 2021) - Nickum, Annie; Thormodson, Kelly; Francis, Marcia
ABSTRACT: The University of North Dakota (UND) School of Medicine & Health Sciences (SMHS) Medical Curriculum Committee (MCC) created the Curriculum Evaluation and Management Subcommittee (CEMS) in 2018. The committee was created to facilitate medical education curriculum content review and revision as discussed in Standard 8.3 of the Liaison Committee on Medical Education (LCME) accreditation standards. The subcommittee consisted of librarians, instructional designers, academic faculty, curriculum team leaders, and a curriculum database manager. The purpose of the group was to recommend policies and best practices to guide writing of learning objectives. The secondary goal for the group was to create a framework for mapping learning objectives within the curriculum and promote detailed mapping of curricular objectives for assessment and continued program accreditation. From the subcommittee's inception, medical librarians advised the group to develop a controlled vocabulary to make curriculum mapping more efficient and led the group in developing one that matched the school's mission and programming.